Struktur Kepemilikan dan Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Indra Siswanti; Embun Prowanta (Universitas Medan Area, 2021)
This study aims to examine the effect of ownership structure on firm value with financial decisions and investment decisions as intervening variables. This study uses secondary data from financial reports. The population used in this study are manufacturing companies in the consumer goods sector which listed on Indonesian stock exchange 2013-2019 of 35 (thirty five) companies. While the research sample was taken using certain criteria.The number of samples obtained are 7 (seven) companies. Data processing techniques using smartPLS 3.0. The results state: 1) ownership structure has a significant effect on firm value, 2) ownership structure has a significant effect on funding decisions, 3) ownership structure has a significant effect on investment decisions, 4) funding decisions has a significant effect on firm value, 5) investment decisions has a significant effect on firm value, 6) funding decisions mediate the effect of ownership structure on firm value, 7) investment decisions mediate the effect of ownership structure on firm value. The limitation of the results of this study is that the results of this study cannot be generalized because the objects used are limited to manufacturing companies in the consumer goods sub-sector.